Case Report: Carcinoma en Cuirasse in a Middle-Aged Woman Mimicking Postirradiation Morphea - Wang, Haiqing; Bao, Chengbei; Gong, Ting; Ji, Chao (Frontiers in Oncology, 2021)
Breast carcinoma en cuirasse (CeC) is an extremely rare form of cutaneous metastases of breast cancer, characterised by diffuse sclerodermoid induration of the skin. It may be difficult to distinguish CeC from some skin diseases, including postirradiation morphea, inflammatory breast cancer, radiation dermatitis, and other cutaneous metastases, but it can be easily discerned by histology. Because of the small number of documented cases, the treatment consensus has not been clearly defined. Here we show a 45-year-old woman with grade III infiltrating ductal carcinoma manifesting as CeC to the chest wall. Early diagnosis and treatment are essential to prevent the catastrophic natural progression of this rare malignancy.